Evaluation of a redesigned self-checkout station for wheelchair users. - Bajaj K; Mirka GA; Sommerich CM; Khachatoorian H (Assistive Technology)
Self-checkout is the emergent/emerging retail technology wherein users (shoppers) check out their own items using an interactive kiosk. A dramatic growth is anticipated in the prevalence of self-checkout systems in retail environments. A study was conducted to develop and evaluate a redesign of a self-checkout system with a focus on issues related to physical accessibility for wheelchair users. Two checkout station prototypes were built: a full-scale model of an existing system and a full-scale model of a system with design modifications (e.g., inclusion of appropriate wheelchair clearance under the workstation, reduced vertical position of the credit card reader, etc.). Five wheelchair users and 10 non-wheelchair users performed simulated self-checkout activities using both workstations. The principal independent variable was workstation type (standard design vs. modified design). The dependent measures were productivity (time to complete a transaction), shoulder flexion angle, torso flexion angle, and the user's subjective assessment of the experience. The results of this study indicate that workstation type did not influence productivity levels in either participant group (wheelchair users or non-wheelchair users). Posture, on the other hand, was significantly improved: the peak shoulder angle was reduced by 64% in wheelchair users and by 69% in the non-wheelchair user group. Peak flexion angle of the torso was also reduced by 67% for wheelchair users. Subjective feedback from the wheelchair user group supported the postural data by showing an overall preference for the redesigned workstation, whereas the non-wheelchair group showed no preference between the two. These results indicate that design for populations with specific limitations does not need to come at a cost of reduced accessibility for persons without these limitations; universal design is achievable.